UPAYA PEMURIDAN BAGI PEMUDA MELALUI METODE KAMBIUM - Tanduklangi, Rinaldus; Tembang, Setblon (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2023)
Abstract. Discipleship is a responsibility mandated by God to the world, especially to the Church. The Church, which is overflowing with the mandate of discipleship, takes a central role in confirming, nurturing and reaching everyone to become disciples of Christ. Youth as an integral part of the church is one of the targets of discipleship that should be considered because they are both a relay and an asset to the church. Discipleship for young people is important so that they are not carried away by the flow of modernity which has the potential to trigger hedonic and materialist attitudes. The KAMBIUM method can be an alternative in reaching youth through discipleship activities. This paper aims to analyze discipleship efforts for youth through the KAMBIUM discipleship method. The research was carried out through a literature study and then the results were analyzed descriptively qualitatively. The conclusion of the research is that the KAMBIUM method is relevant for youth where the pattern of teaching is carried out in three stages namely rooted, growing and bearing fruit in Christ. Abstrak. Pemuridan merupakan tanggung jawab yang diamanatkan Allah kepada dunia khususnya bagi gereja. Gereja yang dilimpahi amanat pemuridan, mengambil peran sentral dalam meneguhkan, memelihara dan menjangkau setiap orang menjadi murid Kristus. Pemuda sebagai bagian integral dari gereja menjadi salah satu sasaran pemuridan yang semestinya diperhatikan sebab mereka adalah estafet sekaligus aset bagi gereja. Pemuridan bagi pemuda penting dilakukan supaya mereka tidak terbawa pada arus modernitas yang berpontensi memicu sikap hedonis dan materialis. Metode KAMBIUM dapat menjadi salah satu alternatif dalam menjangkau pemuda melalui kegiatan pemuridan. Tulisan ini bertujuan untuk menganalisis upaya pemuridan bagi pemuda melalui metode pemuridan KAMBIUM. Penelitian dilakukan melalui study pustaka yang kemudian hasilnya dianalisis secara deskriptif kualitatif. Kesimpulan pada penelitian adalah metode KAMBIUM relevan diterapkan bagi pemuda di mana pola pengajarannya dilakukan dalam tiga tahap yakni berakar, bertumbuh dan berbuah di dalam Kristus.